Zooplankton body composition. (25th September 2013) - Kiørboe, Thomas
Abstract : I compiled literature on zooplankton body composition, from protozoans to gelatinous plankton, and report allometric relations and average body composition. Zooplankton segregate into gelatinous and non‐gelatinous forms, with few intermediate taxa (chaetognaths, polychaetes, and pteropods). In most groups body composition is size independent. Exceptions are protozoans, chaetognaths, and pteropods, where larger individuals become increasingly watery. I speculate about the dichotomy in body composition and argue that differences in feeding mechanisms and predator avoidance strategies favor either a watery or a condensed body form, and that in the intermediate taxa the moderately elevated water content is related to buoyancy control and ambush feeding.